Brother Malcolm, Dr. King, and Black Power – A Close and Complimentary Reading - Fisher, Earle J. (Black theology, 2020)
Rev. Albert Cleage’s contemporary and counterpart, Dr. James Hal Cone, emerged in the late 1960s and early 1970s as a premier academic voice in Black theology. Cone and Cleage’s collegiality is complicated. Yet, their works on Black theology and Black power complement each other when read in contrast. This essay looks intently at excerpts from Cleage’s sermons, “Brother Malcolm,” and “Dr. King and Black Power” and puts them in conversation with excerpts from Cone’s book “Martin and Malcolm in America.” This work shows the variance in perspectives and theological convictions, as well as the rhetorical strategies employed by Cleage and Cone to make their case for the most faithful engagement to Malcolm and Martin’s contributions to civil rights, Black power, and Black theology.